2005
DOI: 10.1103/physrevb.71.020505
|View full text |Cite
|
Sign up to set email alerts
|

Laser-excited ultrahigh-resolution photoemission spectroscopy ofNaxCoO2·yH2O

Abstract: We have studied the temperature-dependent electronic structure near the Fermi level (E F ) of the layered cobaltate superconductor, Na 0.35 CoO 2 ·1.3H 2 O, and related materials, using laser-excited ultrahigh-resolution photoemission spectroscopy. We observe the formation of a pseudogap with an energy scale of ~ 20 meV in Na 0.35 CoO 2 ·1.3H 2 O and Na 0.35 CoO 2 ·0.7H 2 O, which is clearly absent in Na 0.7 CoO 2 . The energy scale of the pseudogap is larger than the expected value for the superconducting gap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 32 publications
4
27
0
Order By: Relevance
“…The preceding ARPES experimental results confirmed that the top postion of the e g band is doping independent, sinking below the Fermi energy, suggesting that it plays no role in the lowenergy phenomena [13][14][15][16][17][18][19][20] . The combined these ARPES experimental results [13][14][15][16][17][18][19][20] and the transport experimental data 6-10 therefore show that the essential low-energy physics of the cobaltates is dominated by the strong electron correlation. The strong-coupling Hubbard model and its equivalent, the t-J model, are prototypes to study the strong correlation effects in solids, especially in connection with the unconventional superconductivity 21,22 .…”
Section: Electron Momentum Distributionsupporting
confidence: 71%
See 2 more Smart Citations
“…The preceding ARPES experimental results confirmed that the top postion of the e g band is doping independent, sinking below the Fermi energy, suggesting that it plays no role in the lowenergy phenomena [13][14][15][16][17][18][19][20] . The combined these ARPES experimental results [13][14][15][16][17][18][19][20] and the transport experimental data 6-10 therefore show that the essential low-energy physics of the cobaltates is dominated by the strong electron correlation. The strong-coupling Hubbard model and its equivalent, the t-J model, are prototypes to study the strong correlation effects in solids, especially in connection with the unconventional superconductivity 21,22 .…”
Section: Electron Momentum Distributionsupporting
confidence: 71%
“…The first principle band calculations predict that the cobaltates have a large EFS centered around the Γ point of the Brillouin zone (BZ) and six small pockets near the K points 11 . However, the angleresolved photoemission spectroscopy (ARPES) measurements on the cobaltates reveal only the large EFS [12][13][14][15][16][17][18][19][20] , while six small EFS pockets near the K points are absent. In particular, these ARPES experimental data also indicate that the area of EFS contains 1 + δ electrons, and therefore fulfills Luttinger's theorem 15,18,20 , where δ is the electron doping concentration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the uniform magnetic susceptibility decreases with decreasing temperature for x ≤ 0.6, while it shows a Curie-Weiss-like behavior for x ≥ 0.6 [3,4]. The quasiparticle spectra in photoemission spectroscopy [5] and optical conductivity in infrared spectroscopy [6] also decrease with decreasing temperature for x ≤ 0.6. It is noteworthy that these "weak pseudogap" behavior is also observed in the normal state of superconducting Na x CoO 2 · yH 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the degree of reduction of DOS is greater when the top of the e ′ g band is just below the Fermi level. In experimental measurements, both uniform spin susceptibility [6] and DOS in the photoemission spectroscpy [7] decrease at lower temperatures. These pseudogap behaviors are consistent with the latter result.…”
mentioning
confidence: 99%